Inflammatory response in chronic degenerative endometritis mares treated with platelet-rich plasma - Reghini, Maria Fernanda S. [UNESP]; Ramires Neto, Carlos [UNESP]; Segabinazzi, Lorenzo G. [UNESP]; Castro Chaves, Maria Manoela B. [UNESP]; Dell'Aqua, Camila de Paula F. [UNESP]; Bussiere, Maria Clara C.; Dell'Aqua, José Antonio [UNESP]; Papa, Frederico O. [UNESP]; Alvarenga, Marco Antonio [UNESP] (Elsevier, 2015)
Degenerative changes of the endometrium are directly related to age and fertility in mares. Chronic degenerative endometritis (CDE) is correlated with uterine fluid retention and reduced ability to clear uterine inflammation. Recent research in the areas of equine surgery and sports medicine has shown that platelet-rich plasma (PRP) treatment acts as an immunomodulator of the inflammatory response. Therefore, the aim of this study was to determine if the uterine infusion of PRP could modulate the local inflammatory response and modify the intrauterine NO concentrations after artificial insemination (AI) in both normal mares and those with CDE. Thirteen mares with endometrium classified as grade III on the histology (mares with CDE) and eight mares with endometrial histological classification I or II-a normal mares were selected to investigate the effect of PRP therapy. The mares were inseminated with fresh semen in two consecutive cycles in a crossover study design. Thereby, each mare served as its own control and the treatment was performed with intrauterine PRP infusion four hours after AI. The percentage of neutrophils in uterine cytology (CIT, %), uterine fluid accumulation observed on ultrasonography (FLU, mm) and nitric oxide concentration of uterine fluid (NO, μM) were analyzed before and 24 hours after AI. The results reported that mares with CDE (CIT, 68.3 ± 3.27, FLU, 10.7 ± 1.61) have a higher (P < 0.05) intrauterine inflammatory response after AI than normal mares (CIT, 24.4 ± 3.56, FLU, 0), but NO concentrations did not differ (P > 0.05) between categories of mares. In treated cycles with PRP, the intrauterine inflammatory response decrease (P < 0.05) in CDE mares (CDE: CIT, 31.4 ± 6.48, FLU, 5.5 ± 1.28; normal mares: CIT, 13.5 ± 4.31, FLU, 0) when compared with nontreated cycle (CDE: CIT, 68.3 ± 3.27, FLU, 10.7 ± 1.61; NM: CIT, 24.4 ± 3.56, FLU, 0), but did not modify NO concentrations in uterine fluid. Thus, we can conclude that PRP was effective in modulating the exacerbated uterine inflammatory response to semen in mares with CDE but did not reduce NO concentrations in intrauterine fluid.
Keywords: Chronic degenerative endometritis; Endometriosis; Mare; Nitric oxide; Platelet-rich plasma